LAS BUSUR UNTUK PENCIPTAAN KARYA 3 DIMENSI PERMUKAAN LENGKUNG BAHAN AS STAINLESS STEEL BENTUK OVAL - Miky Endro Santoso; Elliati Djakaria (Institut Seni Indonesia Yogyakarta, 2020)
This study uses an experimental-descriptive practical research method, focused on the use of arc welding techniques with stainless steel shaft for the creation of 3-dimensional works with curved surfaces. Application for oval form case studies. The purpose of this research is to identify the materials and equipment needed in the welding process with arc welding techniques; know the stages of implementing the creation process starting from preparation, workmanship, and finishing. This experimental-descriptive practice research method was chosen because the researcher was directly involved in the welding experiment process, felt firsthand the level of difficulty and various obstacles in the creation process, and analyzed the results during the research, accompanied by documentation and recording. This research resulted in a 3-dimensional work of art made of stainless steel axles with oval-formed curved surfaces and research conclusions, one of which occurred shrinking the form of the welding results. The results of this research could potentially increase the diversity of art and craft products that use stainless steel axles, such as sculptures, furniture, metal crafts, and so on. Penelitian ini menggunakan metode riset praktik eksperimental-deskriptif, difokuskan pada penggunaan teknik las busur dengan bahan as stainless steel untuk penciptaan karya 3 dimensi dengan permukaan lengkung. Penerapan untuk studi kasus bentuk oval. Tujuan riset ini adalah mengidentifikasi material dan peralatan yang diperlukan dalam proses pengelasan dengan teknik las busur; mengetahui tahapan pelaksanaan proses penciptaan mulai dari persiapan, pengerjaan dan finishing. Metode riset praktik eksperimental-deskriptif ini dipilih karena peneliti terlibat langsung dalam proses eksperimen pengelasan, merasakan secara langsung tingkat kesulitan dan berbagai kendala dalam proses penciptaan serta menganalisis hasil selama riset, disertai dokumentasi dan pencatatan. Riset ini menghasilkan sebuah karya seni 3 dimensi berbahan as stainless steel dengan permukaan lengkung berbentuk oval dan simpulan riset, salah satunya terjadi penyusutan bentuk pada hasil pengelasan. Hasil riset ini berpotensi dapat menambah keberagaman produk seni dan kriya yang menggunakan bahan as stainless steel, seperti patung, furnitur, kriya logam, dan sebagainya.